Takayasu's arteritis. A concise review and some observations on a putative case reported by Giovanni Battista Morgagni (1761) - G. Zanchin; A. Cecchetto; P. Marson; G. Pasero; P. Lazzarin (PAGEPress Publications, 2011)
The discovery of Takayasu's arteritis is likely to date back as far as 1830, owing to the first description of the Japanese Rokushu Yamamoto. Thereafter, several authors from certain geographical areas and in various historical periods described such a vascular disorder, by introducing a quantity of definitions. At present, it is defined as an eponymic disease, namely Takayasu's arteritis, since Makito Takayasu, a Japanese ophtalmologist, reported in 1908 the clinical history of a woman showing some particular retinal anastomotic shunts of arterioles and venules. In the present study the description of an about 40 year-old woman suffering from a pulseless disease, as reported by Giovanni Battista Morgagni in 1761, is summarized. Such a description could be the first case report of Takayasu's arteritis, according to some previous literature data and our critical analysis.